The spiral writing of Julián Ríos - Ripoll (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Experimental writings force us to re-learn how to read. Accustomed to conceiving literature as way of communication between the writer and the reader, as a manifestation of a subject (dogma of expression) or as a description of a specific society (dogma of representation), those texts that create a new universe from language often appear as illegible. That is the case of the texts of Julián Ríos. However, if the reader agrees to consider literature as a reflection and as a way of communicating with other texts that have preceded it, complexity appears as a condition for the reader to become active and to recreate the author’s steps to discover a meaning that is always fugitive. Our article aims, based on some of Julián Ríos' texts, to suggest the uniqueness of a writing that works as a spiral.
Keywords: Spiral; sense; illegible; writing; subversion; language; hybridization; intertextuality